Benefits of physical activity not affected by air pollution: a prospective cohort study. (3rd September 2019) - Sun, Shengzhi; Cao, Wangnan; Qiu, Hong; Ran, Jinjun; Lin, Hualiang; Shen, Chen; Siu-Yin Lee, Ruby; Tian, Linwei
Abstract: Background: Physical activity (PA) is beneficial to human health, whereas long-term exposure to air pollution is harmful. However, their combined effects remain unclear. We aimed to estimate the combined (interactive) mortality effects of PA and long-term exposure to fine particulate matter (PM2.5 ) among older adults in Hong Kong. Methods: Participants aged ≥65 years from the Elderly Health Service Cohort ( n  = 66 820) reported their habitual PA at baseline (1998–2001) and were followed up till 31 December 2011. We used a satellite-based spatiotemporal model to estimate PM2.5 concentration at the residential address for each participant. We used Cox proportional hazards regression to assess the interaction between habitual PA and long-term exposure to PM2.5 on cardiovascular and respiratory mortality. We tested for additive interaction by estimating relative excess risk due to interaction and multiplicative interaction employing P -value for the interaction term. Results: The death risks were inversely associated with a higher volume of PA and were positively associated with long-term exposure to PM2.5 . The benefits of PA were more pronounced for participation in traditional Chinese exercise (e.g. Tai Chi) and aerobic exercise (e.g. cycling). We found little evidence of interaction between PA (volume and type) and long-term exposure to PM2.5 on either additive or multiplicative scales. Conclusions: In this cohort of older Chinese adults, PA may decrease the risk of mortality, be it in areas of relatively good or bad air quality. The beneficial mortality effects of habitual PA outweighed the detrimental effects of long-term exposure to air pollution in Hong Kong.